Odpowiedź :
Odpowiedź:
a) 4 ( 2x-y) + 2 ( 7x+3y )- 12 ( x-y)= 8x -4y +14x +6y -12x +12y= 10x +14y
b) 7b (5+3ax ) - 2bx ( 2a-5b)= 35b +21 abx -4 abx +10 b²x= 10b²x-17abx+35b
c) ( 4a-b) 5 - ( b+2a )9 + 7 ( 3a-4b)= 20a -5b -9b+18a +21a -28b= 59a-42b
d) 12 ( 5a-2) - 8 ( 6a-7b) + 3 ( 3a-12b)= 60a -24 -48a+56b +9a -36b=
=21a+20b-24
Szczegółowe wyjaśnienie:
[tex]a) \ 4(2x-y)+2(7x+3y)-12(x-y) = 8x-4y+14x+6y-12x+12y=10x +14y[/tex]
[tex]b) \ 7b(5+3ax)-2bx(2a-5b) = 35b + 21abx-4abx+10b^{2}x=10b^{2}x + 17abx +35b[/tex]
[tex]c) \ (4a-b)5 -(b+2a)9 + 7(3a-4b) =20a-5b-9b+18a+21a-28b = 59a-42b[/tex]
[tex]c) \ 12(5a-2)-8(6a-7b)+3(3a-12b) = 60a - 24 -48a + 56b + 9a-36b =\\\\= 21a + 20b -24[/tex]